Industrial policy, institutions and industrial financing in South Africa: the role of the IDC and DBSA, and lessons from Brazil's BNDES - Fumbata, Nandipha (Rhodes University, Faculty of Commerce, Department of Economics, 2016)
Institutions, particularly development finance institutions (DFIs) have been instrumental in economic development and the implementation of industrial policy throughout history. In 2007, the South African government identified the country's DFIs as key to the implementation of its new industrial policy framework with the main objective of job creation. This thesis examines the impact that South Africa's DFIs, particularly the IDC and the DBSA, have had on employment creation from 2010 to 2014. A comparative institutional approach is adopted in a case study analysis examining the role of the state in industrial financing. The financing activities of Brazil's BNDES are explored by comparison to determine if there are possible lessons for South Africa. An analysis of the DFIs' financial and annual reports and government policy documents is conducted. The political settlements framework is used as a basis for understanding the balance of power within the country and the impact this has had on the country's industrial policy and industrial finance. The thesis finds that the financing activities of South Africa's DFIs, particularly the IDC, have been directed at large scale capital intensive projects, with a large portion of disbursements channelled towards mining and mineral beneficiation. These sectors have also facilitated the most number of jobs. Even though the activities of the country's DFIs are consistent with South Africa's industrial policy and have facilitated job creation, it is evident that these efforts have not been on a scale that is large enough to reduce unemployment. Despite the DFIs' efforts, there has been an increase in the number of unemployed South Africans between 2010 and 2014.
Keywords: Uncatalogued